Las muchas naturalezas en los Andes - Cavalcanti-Schiel, Ricardo (Perifèria: revista de recerca i formació en antropologia, 2010)
In modern Western thought the idea of nature is constructed in logical opposition to the idea of culture, and with their semantic contents they constitute a specific ecology of mind. I argue here that this arrangement can not necessarily be applicable to others systems of thought. For this purpose I take the case of Andean cosmology and I submit it to an analytical treatment inspired by the “multiculturalistic” thesis from Amazonian ethnology.